Dinamika pelaksanaan Kurikulum 2013 pada tingkat sekolah menengah pertama di Kota Semarang - Wahono, Margi; Wardhani, Novia Wahyu (Jurnal Civics: Media Kajian Kewarganegaraan, 2016)
The purpose of this study was to examine the implementation of the curriculum PPKn 2013 for Junior High School in targeted schools. In details, this research was aimed at (1) describing the influence of curricula across time; (2) describing the dynamics of implementation and its impact on the teachers' understanding; (3) describing the level of teachers' understanding on planning, implementing and evaluating based on curriculum 2013 guidance; and (4) stating a recommendation for curriculum policy makers in future. It was descriptive research. The methods for collecting data were questionnaire, interview, and observation. The results indicated that the teacher understood how to implement the curriculum, especially in teaching PPKn. PPKn teacher was able to plan, conduct, and evaluate of teaching PPKn authentically.